The high-employment route to low inequality - Kenworthy, Lane (Luxembourg, 2010)
"This paper surveys the rise of income inequality in affluent nations. Social programs are critical to keeping inequality in check, but their sustainability is increasingly threatened. A possible solution is high levels of employment. "